Estimating child maltreatment cases that could be alcohol-attributable in New Zealand - Huckle T; Romeo JS (John Wiley & Sons Ltd on behalf of Society for the Study of Addiction, 2023)
Aims Children are an important group harmed by others' alcohol consumption. This study (1) compared the risk of occurrence of child maltreatment among children exposed versus not exposed to parents with an alcohol-attributable hospitalization or service use for mental health/addiction and (2) conducted sensitivity analyses to estimate the cases of child maltreatment that could be attributable to alcohol under two different conditions in New Zealand. Design A cohort study conducted among children 0−17 years and their parents (years 2000–2017) using the Statistics New Zealand Integrated Data Infrastructure. The New Zealand Health Survey 2017 was also used. Setting New Zealand. Participants 58 359 children aged 0–17 years and their parents. Measurements Survival analysis based on a Bayesian piecewise exponential model was used to estimate the risk of time to first substantiated child maltreatment event (identified from social service, hospital, mortality and police data) related to exposure to parents with an alcohol-attributable hospitalization or who used a mental health/addiction service (versus no exposure). Potential confounders were included for parents and children. The sensitivity analyses (i) estimated an alcohol-attributable admissions/service use fraction for maltreatment in 2017 and (ii) calculated a population-attributable fraction using the relative risk from the cohort and prevalence of hazardous drinking (AUDIT 8+) among parents in 2017. Findings There was a 65.1% [1.65; 95% confidence interval (CI) = 1.46−1.86] increased risk of child maltreatment if a child was exposed to parents who had an alcohol-attributable hospitalized or mental health/addictions service use. The sensitivity analyses estimated that in 2017 14.6% (CI = 14.0−15.3%) and 11.4% (95% CI = 8.4−14.3%) of the documented cases of child maltreatment in New Zealand could be attributable to parents with severe or hazardous consumption. Conclusions In New Zealand, exposure to parents with an alcohol-attributable hospitalization or service use is a risk factor for substantiated child maltreatment.
(c) The Author/s 2023
Keywords: alcohol; alcohol policy; child maltreatment; hazardous alcohol consumption; population-attributable fraction; register data; Child; Humans; Cohort Studies; New Zealand; Bayes Theorem; Risk Factors; Child Abuse